HUBUNGAN ANTARA PHYSICAL ATTRACTIVENESS PASANGAN DENGAN KEPUASAN BERPACARAN PADA LAKI-LAKI - Bella, Aulia Nurani (CALYPTRA : Jurnal Ilmiah Mahasiswa Universitas Surabaya, 2016)
Satisfaction is something that is perceived or considered as pleasant. On the dating relationship, satisfaction can define compatibility between expectation and reality are obtained individual to the partner. Medicis Aesthetics (in Diller, 2012) conducted a survey to get an explanation of the physical attractiveness of the long-term role in relation to the more than 1,000 men and women. Results indicate that the more men placed importance on physical attractiveness than women in their relationship. Based on research result, that the physical attractiveness of the partner has implications as role for satisfaction in long-term relationships. This study was conducted to determine whether there is a relationship between physical attractiveness to the satisfaction of dating couples (relationship satisfaction) on the emerging adult males. The subjects with 80 people were males at age 18-25 years. This research method is quantitative correlation and hypothesis testing was done by using a non-parametric correlation (Spearman).